Daya Paham Petani Karet di Desa Kemuja Kecamatan Mendo Barat Kabupaten Bangka terhadap Penggunaan Koagulan Tawas - Sary Wahyuni; Rostiar Sitorus; Rufti Puji Astuti (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
Rubber plants are export commodities that can contribute to efforts to increase Indonesia’s foreign exchange. Rubber, as a leading commodity, has been carried out for a long time by the people of the Bangka Belitung Islands Province as a source of income. Rubber farmers in Indonesia, one of which is in Bangka Regency, namely Kemuja Village, almost all farmers use alum as a rubber coagulant. Based on government regulations, SNI Bokar has set one using coagulants such as Asam ant or Deorub. The people of Kemuja Village once used the coagulant, but the situation did not last long. Various perceptions of farmers on the use of coagulants influence this. This study farmers’ perceptions of using alum coagulants in Kemuja Village, Mendo Barat District. This research was held on November 2021 to June 2022. This study uses the variable perception of 3 indicators: attitudes, interests, and expectations. The research method used is the survey method, which uses the Non Probability Sampling method. The determination of respondents has been carried out intentionally and purposively among as many as 35 respondents. Primary data collection techniques were obtained from interviewing respondents using questionnaires. The method of data analysis used descriptive analysis with a Likert scale. The results showed that the farmer’s perception index score was 66.3 percent, which was positive, consisting of 66.5 percent of attitude indicators perception, 67.4 percent interest, and 64.9 percent hope of using alum as a rubber coagulant.